RELATIONSHIP BETWEEN PARENTAL SUPPORT AND CHILDREN’S ADAPTATION DURING HOSPITALIZATION IN THE PEDIATRIC ROOM OF BHAYANGKARA TK. III HOSPITAL MANADO - Garing, Donita Novianty (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2026)
Background: Hospitalization triggers stress and anxiety that hinder children's adaptation. Parental support helps reduce anxiety and improve adaptation. The family-centered care approach is an essential need in pediatric care. Aim: To analyze the relationship between Parental Support and Child Adaptation during hospitalization in the Pediatric Ward of Bhayangkara Tk. III Hospital Manado. Method: This study used a descriptive method with a cross-sectional approach, involving school-aged children between 7 and 19 years old. This study involved 34 respondents as the sample, selected using a purposive sampling technique. The research data were analyzed using the Spearman Rank statistical test with a significance level of α < 0.005, assisted by the SPSS software. Research instruments included questionnaires on Parental Support and Child Adaptation during hospitalization, both validated and reliable based on previous similar studies. The study was conducted in the Pediatric Ward of Bhayangkara Tk. III Hospital Manado. Results: The Spearman Rank test with an error rate (α) = 0.005 yielded a p-value of 0.001, indicating a significant relationship between Parental Support and Child Adaptation during hospitalization. Conclusion: Children who receive strong parental supportemotional, physical, and accompaniment during caredemonstrate more positive adaptation abilities, such as reduced anxiety, increased sense of security, and more cooperative attitudes toward nursing actions.